Pigmented villonodular synovitis: literature review and case report - L. N. Denisov; V. A. Nesterenko; A. V. Smirnov (Современная ревматология)
Pigmented villonodular synovitis (PVNS) is a rare disease, its diagnosis has certain difficulties. This is due to the absence of characteristic etiological factors and clinical manifestations of PVNS, as well as the insufficient level of knowledge among doctors. The article presents a review of the literature on the diagnosis and treatment of PVNS, as well as a clinical case, which peculiarity is the late diagnosis of this disease, despite the presence of its certain clinical and morphological manifestations.